Haemorrhagic Transformation of a MELAS Stroke-Like Lesion. (18th November 2019) - Bensaidane, Mohamed Reda; Camden, Marie-Christine; Savard, Martin
Abstract : Mitochondrial encephalomyopathy, lactic acidosis and stroke-like episodes (MELAS) is a rare progressive maternally inherited mitochondrial disease that clinically harbours various neurological and systemic manifestations.